Eosinophilic Venulitis in the Small Intestines in a Mouse Model of Late Asthma - Bui, Linh Kan; Hayashi, Toshiharu; Nakashima, Tomomi; Horii, Yoichiro (Inflammation, 2011)
The allergen-unchallenged enteric lesions in late allergic asthma are largely unknown. To clarify this point, BALB/c mice were sensitized by ovalbumin (OVA)/aluminum adjuvant intraperitoneally two times (on days 0 and 10) and then challenged with OVA intranasally on day 14 (asthma group). Four days after the challenge, small intestinal lesions were examined. By this treatment, diarrhea was not observed in the asthma group. Compared to the controls with or without OVA sensitization and/or OVA challenge, the asthma group developed eosinophilic venulitis without an increase in mucosal mast cells in small intestines, whereas intestinal epithelial cells were relatively intact. A few numbers of interleukin (IL)-4 + and IL-5 + lymphoid cells were recognized in intestines in the asthma group, but not in the controls. Expression of vascular cell adhesion molecule-1 on venular endothelium and eotaxin-2 + eosinophils, but not epithelial cells, in intestines were detected in the asthma group, but not in the controls. Total IgE, OVA-specific IgE and eotaxin, and IL-5, but not interferon-γ, were produced systemically in the asthma group compared to the controls. The present study suggests that eosinophilic venulitis without mast cells in the intestine may be induced by the systemic, but not by local, helper T 2-type responses. In addition, eosinophilic venulitis in small intestines may be subclinical enteric lesions.